Polarity of heteroduplex formation promoted by Escherichia coli recA protein. - Kahn, R (1981)
When recA protein pairs circular single strands with linear duplex DNA, the circular strand displaces its homolog from only one end of the duplex molecule and rapidly creates heteroduplex joints that are thousands of base pairs long [DasGupta, C., Shibata, T., Cunningham, R. P. & Radding, C. M. (1980) Cell 22, 437-446]. To examine this apparently polar reaction, we prepared chimeric duplex fragments of DNA that had M13 nucleotide sequences at one end and G4 sequences at the other. Circular single strands homologous to M13 DNA paired with a chimeric fragment when M13 sequences were located at the 3' end of the complementary strand but did not pair when the M13 sequences were located at the 5' end. Likewise circular single-stranded G4 DNA paired with chimeric fragments only when G4 sequences were located at the 3' end of the complementary strand. To confirm these observations, we prepared fd DNA labeled only at the 5' or 3' end of the plus strand, and we examined the susceptibility of these labeled ends to digestion by exonucleases when joint molecules were formed. Eighty percent of the 5' label in joint molecules became sensitive to exonuclease VII. Displacement of that 5' end by recA protein was concerted because it did not occur in the absence of single-stranded DNA or in the presence of heterologous single strands. By contrast, only a small fraction of the 3' label became sensitive to exonuclease VII or exonuclease I. These observations show that recA protein forms heteroduplex joints in a concerted and polarized way.